Prevalence of hypertension in a rural community of coastal Karnataka: a cross sectional study - Saxena, Trapti; K. H., Rajeev (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension is major risk factor for CVDs and its complications account for 9.4 million deaths worldwide every year. Hypertension itself is responsible for about 45% and 51% deaths due to heart disease and stroke respectively. Hypertension is a major public health concern in India both in urban and rural areas and it is increasing at an alarming rate in rural population. Because of inadequate access to health care facilities at rural areas, the early screening and treatment of hypertension is not done regularly, so we conducted this study. The objective of the study was to determine the prevalence of hypertension in a rural community of coastal Karnataka. Methods: A community based cross sectional study was conducted at rural field practice area of Srinivas Institute of Medical Sciences. Sample size was 300 and convenient sampling method used. Data was collected visiting homes and blood pressure measured with mercury sphygmomanometer by. Descriptive statistics were used to analyse the data. Results: Among 300 participants, 45% and 55% were males and females respectively and mean age of the participants was 50.6±15.4 years. The overall prevalence of hypertension among them was 18% and the proportion of hypertension was more among males, people aged >45 years and illiterates. Conclusions: Our study shows that, hypertension has seeped into rural population also which was a concern of the urban population earlier. New cases of hypertension diagnosed were also more which indirectly indicates, most people are not aware of their blood pressure and importance of regular monitoring of blood pressure. So, doing regular screening and creation of awareness at rural areas will help in reducing the morbidity and mortality due to hypertension and its complications.